PENGARUH EFIKASI DIRI, KOMITMEN PROFESIONAL, PENGALAMAN KERJA, DAN SITUASI KONFLIK PERAN TERHADAP KINERJA AUDITOR - Triana Yuniati; Cahyadi Husadha; Futriwati (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
The population in this study were the employee auditors at the Public Accounting Firm (KAP), with a sample size of 80 auditors. The questionnaire was distributed directly using hardcopy to the worker auditors at the Public Accounting Firm (KAP). The methodology in this research is using the method of probability sampling and purposive sampling stage. The results of the study partially show that Self-Efficacy has no effect on Auditor Performance; t-test results obtained a significance value of 0.263> 0.05. Professional Commitment affects Auditor Performance; t-test results obtained a significance value of 0.003 <0.05. Work experience has an effect on Auditor Performance; t-test results obtained a significance value of 0.038 <0.05. And the role conflict situation affects the performance of the auditor; t-test results obtained a significance value of 0.026 <0.05. Meanwhile, the results of the research simultaneously show that Self-Efficacy, Professional Commitment, Work Experience, and Role Conflict Situations together have an effect on Auditor Performance; f-test results obtained a significance value of 0.004 <0.05.